Microscopic Evaluation of Leaves of Memecylon umbellatum Burm - Suresh G. Killedar; Harinath N. More; Sameer J. Nadaf (Advances in Agriculture)
Objective. Aim of present work is to perform the microscopic evaluation and physicochemical analysis and to explore the morphology parameters of Memecylon umbellatum Burm leaves. Methods. Fresh, dried and desiccated powdered leaf samples were studied for their morphology, microscopy, organoleptic characters, and an assortment of other WHO recommended methods for standardisation. Results. The microscopy revealed the dorsiventral nature of the leaf. Midrib showed presence of nonlignified phloem, lignified xylem with well-defined xylem fibers, vessels, and parenchyma. Presence of Phloecentric vascular bundles surrounded by endodermis and crystal sheath. Well-defined patches of collenchyma were observed above and below the vascular bundles in the midrib area. Trichomes are mostly absent and stomata (anomocytic) were observed on both epidermal surfaces. Conclusions. It can be concluded that the microscopic analysis and pharmacognostic parameters can serve as tool for developing standards for proper authentication, quality, and purity of Memecylon umbellatum Burm leaves.